2017
DOI: 10.1002/mp.12065
|View full text |Cite
|
Sign up to set email alerts
|

An MRI‐compatible patient rotation system — design, construction, and first organ deformation results

Abstract: An MRI-compatible patient rotation system has been designed, constructed, and tested. A pelvic study was carried out on a healthy volunteer. Rigid registration based on the prostate contour yielded DSC overlap statistics in the prostate superior to interobserver contouring variability reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…Immobilization improves with increasing airbag pressure as expected, though vertical displacement due to gravity cannot be entirely avoided. Real‐time image guidance could be used to measure and compensate for the vertical displacement, as well as for internal organ deformation due to gravity …”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Immobilization improves with increasing airbag pressure as expected, though vertical displacement due to gravity cannot be entirely avoided. Real‐time image guidance could be used to measure and compensate for the vertical displacement, as well as for internal organ deformation due to gravity …”
Section: Resultsmentioning
confidence: 56%
“…This situation does not represent the real use case, where patients undergoing horizontal rotation will be subject to varying amounts of vertical displacement (shown in Fig. ) and internal organ deformation due to gravity . Three essential steps would need to be taken to deliver the 3D conformal treatments described in this manuscript to human patients.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28] As such, it is not unreasonable to hypothesise that anatomic deformation resulting from rotation could be adapted for. In modern radiotherapy, it is becoming increasingly common to measure and adapt for patient motion, and there is already a great deal of research focused on increasing this capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In modern radiotherapy, it is becoming increasingly common to measure and adapt for patient motion, and there is already a great deal of research focused on increasing this capacity. [23][24][25][26][27][28] As such, it is not unreasonable to hypothesise that anatomic deformation resulting from rotation could be adapted for. However, if patient rotation is to be clinically adopted, future studies will have to quantify patient deformation under rotation, and develop techniques to deliver high-quality radiotherapy in the presence of such deformation.…”
Section: Discussionmentioning
confidence: 99%
“…4 . 14 A previous publication by Whelan et al 2 showed that rotating a carefully immobilised healthy volunteer by increments of 45°around the craniocaudal axis produced pelvic tissue deformations sufficient to require the adoption of 'an adaptive radiotherapy technique' to ensure accurate delivery of the planned treatment. .do not rotate the lying patient.…”
mentioning
confidence: 99%